A Novel Spectrometer for Measuring Laser-Produced Plasma X-Ray in Inertial Confinement Fusion. (26th August 2012) - Gang, Zhu; Xian-cai, Xiong; Xian-xin, Zhong; Yan, Yang
Abstract : In the experimental investigations of inertial confinement fusion, the laser-produced high-temperature plasma contains very abundant information, such as the electron temperature and density, ionization. In order to diagnose laser-plasma distribution in space and evolution in time, an elliptical curved crystal spectrometer has been developed and applied to diagnose X-ray of laser-produced plasma in 0.2 ~ 2.46 nm region. According to the theory of Bragg diffraction, four kinds of crystal including LiF, PET, MiCa, and KAP were chosen as dispersive elements. The distance of crystal lattice varies from 0.4 to 2.6 nm. Bragg angle is in the range of 30° ~ 67.5°, and the spectral detection angle is in 55.4° ~ 134°. The curved crystal spectrometer mainly consists of elliptical curved crystal analyzer, vacuum configuration, aligning device, spectral detectors and three-dimensional microadjustment devices. The spectrographic experiment was carried out on the XG-2 laser facility. Emission spectrum of Al plasmas, Ti plasma, and Au plasmas have been successfully recorded by using X-ray CCD camera. It is demonstrated experimentally that the measured wavelength is accorded with the theoretical value.